2004
DOI: 10.1038/sj.embor.7400073
|View full text |Cite
|
Sign up to set email alerts
|

Parasite‐specific immune response in adult Drosophila melanogaster: a genomic study

Abstract: Insects of the order Diptera are vectors for parasitic diseases such as malaria, sleeping sickness and leishmania. In the search for genes encoding proteins involved in the antiparasitic response, we have used the protozoan parasite Octosporea muscaedomesticae for oral infections of adult Drosophila melanogaster. To identify parasite-specific response molecules, other flies were exposed to virus, bacteria or fungi in parallel. Analysis of gene expression patterns after 24 h of microbial challenge, using Affyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 24 publications
8
103
3
Order By: Relevance
“…A second point of importance will be the identification of antiviral molecules in Drosophila. Finally, it seems appropriate to study the immune response after natural viral infection because the route of entry may influence the host response: Only few genes were induced in microarray studies after oral ingestion of DCV (266), in contrast to the robust response observed after DCV injection (91).…”
Section: Drosophila C Virus (Dcv)mentioning
confidence: 99%
“…A second point of importance will be the identification of antiviral molecules in Drosophila. Finally, it seems appropriate to study the immune response after natural viral infection because the route of entry may influence the host response: Only few genes were induced in microarray studies after oral ingestion of DCV (266), in contrast to the robust response observed after DCV injection (91).…”
Section: Drosophila C Virus (Dcv)mentioning
confidence: 99%
“…pes is required for the uptake of Mycobacterium smegmatis and Listeria monocytogenes by macrophages (Philips et al, 2005), and its expression in midgut and salivary glands has been previously described (Cao et al, 2007;Li et al, 2009). CG2736 appears to be part of the D. melanogaster lipid droplet subproteome (Beller et al, 2006), being induced by infection with Octosporea muscaedomesticae (Roxstrom-Lindquist et al, 2004) and upregulated in fly stocks resistant to infection with Pseudomonas aeruginosa, as well as CG10345 (Ye et al, 2009). In the case of Snmp, it is required for pheromone sensitivity in Drosophila and it is implicated in the reception of 11-cis-vaccenyl acetate (cVA), which mediates a variety of behaviours including aggregation, mate recognition and sexual behaviour.…”
Section: Fig 5 Temporal Regulation Of the Sr-bis In Non Esteroidogementioning
confidence: 99%
“…Further, only male physiology has been used in the genomics-based approaches to immune response genes. [12][13][14] In this work, we present a baseline comparison that begins to address the issues and opportunities afforded by studying both sexes. Our experiments assess post-infection survival against the commonly studied microorganisms Beauveria bassiana and E. coli, and the results show a dichotomy between the sexes.…”
Section: Introductionmentioning
confidence: 99%